Insurance, redistribution, and the inequality of lifetime income - Peter Haan; Daniel Kemptner; Victoria Prowse (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
Individuals vary considerably in how much they earn during their lifetimes. We study how the tax-and-transfer system o sets inequalities in lifetime earnings, which would otherwise translate into differences in living standards. Based on a life-cycle model, we find that redistribution by taxes and transfers off sets 54% of the inequality in lifetime earnings that is due to heterogeneous skill endowments. Meanwhile, taxes and transfers insure 45% of lifetime earnings risk. Taxes would provide more insurance if based on lifetime instead of annual earnings. Requiring wealthy individuals to repay social assistance received when younger would strengthen the insurance and redistributive functions of social assistance.
Keywords: D63; H23; I24; I38; J22; J31; 330; Lifetime earnings; lifetime income; tax-and-transfer system; taxation; unemployment insurance; disability benefits; social assistance; inequality; redistribution; insurance; endowments; risk; dynamic life-cycle models